A Retrospective Analysis of Eclampsia as a Major Cause of Maternal and Perinatal Mortality in Sagamu - Sotunsa JO; Inofomoh AI; Akinseku AI; Ani FI; Sule-Odu AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2015)
Background: While eclampsia remains a leading cause of maternal death in the developing world, the prevalence and case fatality of the condition in the developed world has reduced due to early detection and prompt treatment. The understanding of the factors associated with eclampsia may reduce the burden and enhance the quality of foeto-maternal outcome. Objective: To determine the prevalence of eclampsia and the associated foeto-maternal outcome. Methods: A retrospective study of patients who presented with eclampsia at the Olabisi Onabanjo University Teaching Hospital (OOUTH) between January 2008 and December 2012 was carried out. The hospital records were retrieved and the data extracted included the age, parity, gestational age at presentation, booking status, mode of delivery, outcome of baby and mother, and the total delivery in the hospital over the period. Results: The prevalence of eclampsia over the period was 1.1%. Eclampsia was common among women aged 25years and below (64.3%), nulliparous women (78.6%) and unbooked (100.0%). Caesarean section was carried out on 63.0% of the patients on account of unfavourable cervix, while 22.2% of patients had spontaneous vagina delivery. Most (96.4%) received magnesium sulphate (MgSO4) therapy but 22.2% convulsed while receiving it. Maternal mortality was 7.1% while perinatal mortality rate was 250/1000 live birth. Conclusion: Eclampsia remains a cause of maternal morbidity and preventable death in the understudied community. Early antenatal booking and the use of MgSO4 are effective in reducing the burden.